Change management in the organization: basic concepts and models - O.V. Tarasiuk (Економіка, управління та адміністрування)
The question of the genesis of the formation of change management models in the organization was studied. Under the conditions of martial law in Ukraine, the most relevant HR priorities of companies are workload management (57 %), real-time support and assistance to employees (57 %) and revision of the headcount/organizational structure (49 %). The majority of companies (67 %) have not changed the number of employees since the beginning of the full-scale war. About half of them (54 %) do not plan to review within the next 3 months. About 28 % of companies reduced their workforce, with a median of 10 %. The most common reason was the forced migration/relocation of workers. The biggest challenges in wartime people management are worker safety (74 %), maintaining team productivity (56 %) and ensuring continuity of work processes (49 %). Taking these factors into account, it is proven that change management requires flexibility and adaptability, analysis of existing change management models and selection of the model that will be more acceptable for business entities. According to the results of the study, the characteristics of change management models were determined, which are grouped according to the main features: approach, content, mechanism, impact on personnel and application possibilities. An analysis of modern change management methodologies was carried out, in particular according to the PCI (People-Centred Implementation) model. It was determined that the integrated model of change management is appropriate to use in organizations with a high level of resistance to change, where beliefs, motivation and flexibility are important. Organizations need to listen to employees and share information about industry trends, leadership ideas, best practices and competitor analysis. This will help everyone understand why the changes are necessary. The expediency of combining change management models and advanced practices of their implementation has been proven. A combination of Gleicher’s formula with additional models, such as Kotter’s 8-step model or ADKAR or the PCI (People-Centred Implementation) model, is proposed, which can maximally take into account the strengths and weaknesses of implementing changes in organizations.